1992
DOI: 10.1051/rnd:19920402
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of maize stem by two rumen fungal species, Piromyces communis and Caecomyces communis, in pure cultures or in association with cellulolytic bacteria

Abstract: Summary ― Two species of rumen fungi, Piromyces (Piromonas) communis FL and Caecomyces (Sphaeromonas) communis FG10, were cultured alone or in association with the cellulolytic bacteria Ruminococcus flavefaciens or Fibrobacter succinogenes on maize stem. A kinetic study of the degradation of the substrate was then made. After 48 h of culture, all non-lignified tissues observed by scanning electron microscopy disappeared with P communis and degradation was as complete as that observed in the rumen. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 12 publications
2
8
0
1
Order By: Relevance
“…In contrast to the range of cell types in xylem cylinders colonized by N. frontalis and P. communis , C. communis showed very specific colonization of the secondary xylem fibres. A similar observation was made by Roger et al. (1992) for a strain of C. communis colonizing lignified tissues of Zea mays stem.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast to the range of cell types in xylem cylinders colonized by N. frontalis and P. communis , C. communis showed very specific colonization of the secondary xylem fibres. A similar observation was made by Roger et al. (1992) for a strain of C. communis colonizing lignified tissues of Zea mays stem.…”
Section: Discussionsupporting
confidence: 80%
“…flavefaciens and two out of three strains of R. In co-cultures grown on cellulose, demonstrated that R. fiavefaciens was not antagonistic towards C. communis but inhibited cellulolysis by N. frontalis and P. communis. In contrast, in studies on maize stem degradation by fungi, Roger et al (1992) found no inhibition of P. communis or C. communis by R. fiavefaciens (or by F. succinogenes). (There was no inhibitory activity from either of two strains of F. succinogenes on the mixed fungi.)…”
Section: Fungal Interactions With Rumen Bacteriamentioning
confidence: 86%
“…The recalcitrant lignocellulosic structures that are the most difficult to degrade are generally those that are the most abundantly colonized (Akin, 1987;Bauchop, 1989;Grenet and Barry, 1988). In addition, anaerobic fungi have the necessary array of enzymes to degrade all plant cell wall polymers except lignin (Williams and Orpin, 1987;H6braud and F6vre, 1988 Bernalier et al, 1992Bernalier et al, , 1993Stewart et al, 1992;Roger ef al, 1993). The species composition of the ruminal cellulolytic microflora harboured by the lambs was not determined, but it was probable that the ruminococci were members of this population.…”
Section: Enzyme Assay Proceduresmentioning
confidence: 99%
“…Any attempt to optimize rumen function, notably experiments designed to improve degradation of the cellwall polymers, cellulose and hemicellulose, will require a fuller understanding of the role and activity of the different hydrolytic microorganisms. There have been numerous studies on the activity of the main fungal and cellulolytic bacterial species in vitro (Fonty et al, 1988a;Orpin and Joblin, 1988;Stewart and Bryant, 1988;Fonty and Joblin, 1991) and their interactions in cellulolysis have been studied in cocultures (Bernalier et al, 1992(Bernalier et al, , 1993Roger et al, 1992Roger et al, , 1993Stewart et al, 1992;Williams et al, 1994 (Mann and Stewart, 1974;Lysons et al, 1976;Hobson et al, 1981;Fonty et al, 1983Fonty et al, , 1988b. Nevertheless, the activity of the 3 main cellulolytic bacterial species, Fibrobacter (Bacteroides) succinogenes, Ruminococcus flavefaciens and R albus, alone or in association, and that of of a fungal flora have been studied in newborn lambs (Fonty et al, 1988c; …”
Section: Introductionmentioning
confidence: 99%